Long Non-coding RNA LINC01094 Promotes the Development of Clear Cell Renal Cell Carcinoma by Upregulating SLC2A3 via MicroRNA-184 - Xu, Haifei; Wang, Xiaolin; Wu, Jiacheng; Ji, Hao; Chen, Zhigang; Guo, Haifeng; Hou, Jianquan (Frontiers in Genetics, 2020)
Clear cell renal cell carcinoma (ccRCC) is the most common subtype of RCC. Compelling evidence has highlighted the crucial role of long non-coding RNA (lncRNA) in ccRCC. Our current study aims to explore the regulatory mechanism of LINC01094 in the development of ccRCC. Dual-luciferase reporter experiment verified the targeting relationship among miR-184, LINC01094, and SLC2A3. Furthermore, the interaction between LINC01094 and miR-184 was confirmed by RIP and RNA pull-down. Biological behaviors of ccRCC cells were investigated through Cell Counting Kit-8 (CCK8), scratch test, Transwell, and flow cytometry. The effect of SLC2A3 on the tumorigenicity of nude mice was evaluated in vivo. In ccRCC cells and clinical tissues, LINC01094 and SLC2A3 were highly expressed while miR-184 was lowly expressed. Besides, miR-184 was verified to be a direct target of LINC01094. Silencing LINC01094, upregulating miR-184, or reducing SLC2A3 inhibited the growth, migration, and invasion of ccRCC cells. Tumor growth was suppressed by silenced LINC01215 via reducing the expression of SLC2A3 via miR-184. Taken together, silencing LINC01094 inhibited SLC2A3 expression by upregulating miR-184, thereby inhibiting the development of ccRCC.